2020
DOI: 10.1101/2020.04.27.063180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of replicating SARS-CoV-2 polymerase

Abstract: The coronavirus SARS-CoV-2 uses an RNA-dependent RNA polymerase (RdRp) for the replication of its genome and the transcription of its genes. Here we present the cryo-electron microscopic structure of the SARS-CoV-2 RdRp in its replicating form. The structure comprises the viral proteins nsp12, nsp8, and nsp7, and over two turns of RNA template-product duplex. The active site cleft of nsp12 binds the first turn of RNA and mediates RdRp activity with conserved residues. Two copies of nsp8 bind to opposite sides … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(200 citation statements)
references
References 34 publications
8
191
0
1
Order By: Relevance
“…The field of COVID‐19 therapeutics development is moving rapidly, and while this manuscript was under review and revision, numerous publications and preprints have appeared. Structural studies have indicated possible binding sites in the SARS‐CoV‐2 RdRp for potential polymerase inhibitors 48‐52 . Given the high homology of the SARS‐CoV and SARS‐CoV‐2 RdRp active site domains, it is likely that they will bind nucleotide analogues such as Sofosbuvir in a similar way, as we have recently reported 46 .…”
Section: Resultsmentioning
confidence: 64%
“…The field of COVID‐19 therapeutics development is moving rapidly, and while this manuscript was under review and revision, numerous publications and preprints have appeared. Structural studies have indicated possible binding sites in the SARS‐CoV‐2 RdRp for potential polymerase inhibitors 48‐52 . Given the high homology of the SARS‐CoV and SARS‐CoV‐2 RdRp active site domains, it is likely that they will bind nucleotide analogues such as Sofosbuvir in a similar way, as we have recently reported 46 .…”
Section: Resultsmentioning
confidence: 64%
“…Although retroviruses such as HIV use reverse transcriptase (estimated error rate at 10 −3 misincorporations per nucleotide position per genome replication) during their replication [ 74 ], SARS-CoV-2 uses a higher-fidelity RdRp (with an estimated error rate of 10 −4 to 10 −5 misincorporations per nucleotide position per genome replication) [ 75 ]. Hence, SARS-CoV-2 may be less prone to incorporate mutations [ 76 ]. However, a broad mutation spectrum of SARS-CoV-2 has been observed, which could lead to vaccine and drug resistance [ 77.…”
Section: Challenges In the Successful Development Of Neutralizing Antmentioning
confidence: 99%
“…SARS-CoV-2 is an enveloped, pleomorphic or spherical shaped positive sense RNA virus having varying genome length of around 30 kb with a 5′- cap structure and 3′- poly A tail with an arrangement as 5′-replicase open reading frame (ORF) 1ab-spike( S )-envelope( E )-membrane(M)-N-3′ [ 13 , 14 ]. Population genetics analysis of 103 SARS-CoV-2 genomes indicate that these viruses have evolved into two major lineages namely the more prevalent CT haplotype or the L lineage and the TC haplotype also called the S lineage [ 15 ].…”
Section: Structure and Pathogenesis Of Sars-cov-2mentioning
confidence: 99%